A Research-based Approach to Identify the Health-conscious Consumers in India. Issue 2 (December 2022) - Menon, Sindhu R.; Chavadi, Chandan A.
With the current pandemic, the health-conscious consumer segment, a niche segment, has emerged as a major market for a range of products and services. It is necessary for marketers to identify and profile the health-conscious consumers in the country to devise the right segmentation, targeting, and positioning (STP) strategy and to design a consumer-centric marketing mix. The scales used to measure health consciousness and related concepts are developed and tested in the West and there is no such scale that fits India's demographic and cultural context. The objective of this study was to conceptualize a reliable health consciousness scale that is relevant to India. This was a quantitative study that was conducted in April–May 2021. Items to be included in the scale were derived based on the review of existing literature and brainstorming among target respondents. Confirmatory factor analysis was used for data reduction. A series of principal component factor analyses using Varimax yielded 12 scale items that loaded onto three factors—health involvement, health responsibility, and health awareness. Scale items were tested for validity and reliability—measures tested include Cronbach's alpha, composite reliability, discriminant validity, and average variance extracted. SPSS version 20 and AMOS version 20 were used to analyse data. This study yielded a health consciousness scale that can be used to identify health-conscious consumers in India.